Perbandingan Motivasi Belajar Siswa pada Pembelajaran IPS Secara Daring dan Tatap Muka - Syarifuddin, Syarifuddin Social Studies Postgraduate Study; Aisyah, Siti; Triana, Yuli (UNIB Press, 2023)
This study aims to compare student learning motivation in online and face-to-face social studies learning and explore strategies that can increase student motivation in these subjects. This study uses the literature review method by analyzing past and recent research findings that are relevant to the research topic. The results showed that there was no significant difference in learning motivation between students in online and face-to-face social studies learning. However, there are several strategies that can be implemented to increase student motivation, such as facilitating interaction between students and teachers, providing positive feedback, and creating interesting and relevant learning materials. The recommendation from this study is for teachers to apply these strategies in social studies learning to increase students' learning motivation.